[New WHO classification 2022: urinary bladder cancer]. - Gaisa, Nadine Therese; Hartmann, Arndt; Knuechel-Clarke, Ruth (Die Pathologie, 2023)
The new World Health Organization (WHO) classification of urogenital tumors is still primarily based on anatomic location, but is also a hierarchical taxonomic classification without separate chapters for tumors of the upper urinary tract and the urethra. It clarifies aspects regarding grading and noninvasive entities. It consolidates the use of the Paris system for urinary cytology as well as various subtypes/special types of neoplasms, and incorporates general concepts of the 5th edition of the WHO blue book. In addition to mesenchymal tumors, well-differentiated neuroendocrine tumors and neuroendocrine carcinomas are addressed in separate chapters. Papillary non-invasive low- and high-grade carcinomas and carcinoma in situ remain, while dysplasia and urothelial proliferation of unknown malignant potential (UPUMP) are no longer treated as separate entities. Former variants of urothelial carcinoma are now called subtypes and aberrant differentiation and special types are more precisely defined.
EVALuna2:536073